Sacred Marriage What if God Designed Marriage to make us Holy More than to Make Us Happy? - Thomas, Gary (Gary Lee) (Grand Rapids Zondervan Publishing House, 2000)
"'Sacred Marriage' doesn't tell how to build a better marriage--it shows how your marriage can help you deepen your relationship with God. From the practice of forgiveness, to the ecstasy of lovingmaking, to the history you and your spouse create togeth
"Now with discussion questions"--Page 4 of cover.
Keywords: Spouses -- Religious life -- Christianity. Marriage -- Religious aspects -- Christianity. Spiritual life -- Christianity